A reflection on tactical urbanism, marginal periphery and citizen participation (REVISTA NODO, 2021)
This paper presents some theoretical elements that are part of the conceptual framework of the research project “Tactical interventions in marginal peripheries and citizen appropriation of the Polvorín de San Juan de Pasto sector, Colombia”; whose objective was to determine the impacts and incidents of these categories in local realities, in the ways of inserting cutting-edge initiatives and methodologies that are also related to the physical and spatial aspects and their immediate impacts in the search for urban developments as an aesthetic reference, which can become another way of rethinking the problems of peripheral settlements. The project in question started from an research initiative between the Catholic University of Pereira and the María Goretti University Center for Higher Studies (CESMAG) that initially sought to develop a proposal for physical, spatial and socio-cultural intervention from the participatory perspective in the neighborhoods El Rocío Alto and Caracol la Curva, from Pereira and El Polvorín, from Pasto (Colombia). However, so far only the experience in the latter sector has been carried out. Taking into account the above, the purpose of this essay is to present a theoretical reflection on tactical urbanism and citizen participation in marginal environments where aspects such as exchange of use, daily memories, the valuation of underused interstices and the search become important of an appropriation by the community in the restoration of the existing urban landscape.
Keywords: Urban design; Community participation; Urban Zone; Urban decentralization; Urban planification